Implementasi Metode User Centered Design Di Ma'had Tahfidz Quran Darussalam - Tesa Anggraini; Eriene Dheanda Absharina; Zainal Effendi; Harisdianto; Anggari Ayu Prahartiningsyah (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
This study discusses the development of a web-based student data application at Mah’ad Tahfidz Qur’an Darussalam using the User Centered Design (UCD) theory. User Centered Design is a system development approach that focuses on user involvement at every stage of the design process to ensure that the resulting system meets user needs. Previously, student data management at Mah’ad Tahfidz Qur’an Darussalam was still carried out manually using paper records and Microsoft Excel, so the data management process had not been effective and efficient. This study was conducted to produce a student data application that can support a more structured and integrated data management process. The method used is User Centered Design (UCD), which includes data collection through interviews and documentation, user requirement analysis, system design, application implementation, and usability testing using the System Usability Scale (SUS). The developed application is able to manage student data, Qur’an memorization data, teacher data, as well as facilities and infrastructure data. Based on the testing conducted, the application shows a good level of usability and is able to support users in managing data more easily and quickly. Keywords: Data Santri,  Information System, Usability, User-Centered Design, and Ma’had Tahfidz Quran